Evaluation of a carbohydrase (xylanase and glucanase) enzyme complex in diets for Florida pompano Trachinotus carolinus - Stites, William; Weldon, Alexis; Reis, João; Ito, Paulo [UNESP]; Rhodes, Melanie; Davis, D. Allen (Wiley, 2024)
Florida pompano, Trachinotus carolinus, can be fed soy-based, low-animal protein diets. However, anti-nutritional factors and carbohydrates limit digestibility. Dietary carbohydrase enzymes have been used to improve carbohydrate digestibility in several species and may be beneficial for Florida pompano. The present study was designed to evaluate the effects of using a carbohydrase enzyme complex (Natugrain® TS L, BASF Corporation, Ludwigshafen, Germany) composed of endo-1,4-ß-xylanase and endo-1,4-ß-glucanase (Xyl + Glu) on growth performance, feed utilization, and digestibility in diets fed to juvenile Florida pompano. A growth trial was conducted with iso-nitrogenous (40%) and iso-lipidic (8%) test diets containing 0, 0.015, 0.030, and 0.045% of Xyl + Glu. The trial was conducted in a recirculating system with 12, 1000-L tanks. Twenty fish (mean weight: 23.34 g ± 1.49 g) were stocked into each tank in a randomized design. Growth results indicated that there were no significant differences (p > 0.05) in growth and feed conversion; however, thermal growth coefficient displayed significant differences (p = 0.0499) between the 0.015 and 0.030% inclusion. All enzymatic treatments displayed significant differences (p = 0.029) in apparent digestibility of crude protein compared with the basal diet. Results indicate that Xyl + Glu enzyme complex can impact protein digestibility but did not significantly affect growth performance.
Keywords: carbohydrase; digestibility; exogenous enzymes; glucanase; pompano; xylanase